1968
DOI: 10.1515/mamm.1968.32.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and Recruitment Patterns in Warthog (Phacochoerus Aethiopicus) Populations

Abstract: La reproduction et le taux de rcnouvellement des populations de phacochores ont eto otudics dans le pörimetre de lütte antitsetso de Nagupande (Rhodosie) et compares avcc d'autres observations effectuees en Afrique du Sud et avec cclles existant dans la litterature.A Nagupande le rut sc situe en mal et la mise-bas en octobrc ou novembre. L'allaitement du re 3 a 4 mois, mais n'a probablement qu'une importance rlduite apres les 8*9 premieres scmaines. La maturite sexuelle intervicnt a la fin de la premiere annce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

1972
1972
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
3
12
0
1
Order By: Relevance
“…13 suggests a rapid build up in the weight of the testicles in adults from a low in August to a peak just before the rut. Similar seasonal fluctuations in impala (Kerr, 1965 ;Child, 1968) and warthog (Child et α Ζ., 1968) are associated with differences in the amount of spermatogenesis. If this also applies in tsessebe, it would infer that, as in the other two species, the timing of the reproductive cycle is to some extent dependent on the seasonal synchronization of gamete production in both sexes.…”
Section: Malesmentioning
confidence: 88%
See 2 more Smart Citations
“…13 suggests a rapid build up in the weight of the testicles in adults from a low in August to a peak just before the rut. Similar seasonal fluctuations in impala (Kerr, 1965 ;Child, 1968) and warthog (Child et α Ζ., 1968) are associated with differences in the amount of spermatogenesis. If this also applies in tsessebe, it would infer that, as in the other two species, the timing of the reproductive cycle is to some extent dependent on the seasonal synchronization of gamete production in both sexes.…”
Section: Malesmentioning
confidence: 88%
“…Acacia woodland occurs on some of the sandiest soils, while open grassland is associated with areas of impeded drainage. A more detailed account of the topography and vegetation of the Chobe National Park is given by Child (1968 a).…”
Section: The Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, calving in topi in the Mara and Serengeti (Sinclair et al 2000) is synchronized, but less so than in its congenerics in Southern Africa, with one rainy season (Fairall 1968;Du Plessis 1972;David 1975), but is bimodal in some equatorial populations (Estes and Estes 1979). Timing of breeding in warthog also varies considerably geographically with distinct farrowing seasons reported for parts of Eastern (Child et al 1968;Leuthold and Leuthold 1975;Boshe 1981;Rodgers 1984;Sinclair et al 2000) and Southern (Mason 1986) Africa, and bimodal or continuous breeding for Zaire and Congo Braziville, with high rainfall year-round (Brown 1936). If breeding in ungulates is determined by the quantity and quality of forage (Sadleir 1969), then onset of births should be delayed in dry and advanced in wet relative to an average year.…”
Section: Timing Of Birthsmentioning
confidence: 99%
“…Timing of conception in African savanna ungulates appears determined by rainfall (Child et al 1968;Boshe 1981) acting through maternal body condition, because high rainfall improves forage quantity and quality (Desmukh 1984). Post et al (2003) also reported clear synchronization of the timing of parturition by caribou to plant phenology, regardless of predation pressure, suggesting that food sufficiency also governs the timing and spread of births in northern ungulates.…”
Section: Timing Of Birthsmentioning
confidence: 99%